Lost in translation? Can the use of theories of action be effective in helping teachers develop and scale up research-informed practices?. (May 2018) - Brown, Chris; Flood, Jane
Highlights: Teachers need to tailor interventions to meet the specifics of their context. Theories of action (ToAs) can help teachers localise research based interventions. A ToA approach was employed with three primary schools. An evaluation of the TOA approach shows it improves teaching practice. Using ToAs also results in impactful interventions for students.